2013
DOI: 10.1242/jcs.118828
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B promotes focal complex maturation, lamellar persistence and directional migration

Abstract: SummaryPrevious findings established that ER-bound PTP1B targets peripheral cell-matrix adhesions and positively regulates cell adhesion to fibronectin. Here we show that PTP1B enhances focal complex lifetime at the lamellipodium base, delaying their turnover and facilitating a-actinin incorporation. We demonstrate the presence of catalytic PTP1BD181A-a-actinin complexes at focal complexes. Kymograph analysis revealed that PTP1B contributes to lamellar protrusion persistence and directional cell migration. Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 84 publications
(107 reference statements)
6
47
0
Order By: Relevance
“…In support to this notion, Bimolecular Fluorescence Complementation (BiFC) analysis revealed the presence of catalytic PTP1B/α-actinin complexes overlapping with paxillin adhesions at lamellar extensions. 28 In addition, we observed that small paxillin adhesions assembled during lamellar protrusion in KO cells did not incorporate α-actinin efficiently and were quickly disassembled. 28 In contrast, most adhesions assembled during lamellar protrusion in WT cells incorporated α-actinin and grew in size.…”
Section: Ptp1b Regulation Of Cell-matrix Coupling To the Cytoskeletonmentioning
confidence: 76%
See 3 more Smart Citations
“…In support to this notion, Bimolecular Fluorescence Complementation (BiFC) analysis revealed the presence of catalytic PTP1B/α-actinin complexes overlapping with paxillin adhesions at lamellar extensions. 28 In addition, we observed that small paxillin adhesions assembled during lamellar protrusion in KO cells did not incorporate α-actinin efficiently and were quickly disassembled. 28 In contrast, most adhesions assembled during lamellar protrusion in WT cells incorporated α-actinin and grew in size.…”
Section: Ptp1b Regulation Of Cell-matrix Coupling To the Cytoskeletonmentioning
confidence: 76%
“…Visual inspection of cell morphology and kymograph analysis of the leading edge further revealed that migration of KO cells was characterized by fast extension/retraction of lamella produced in multiple directions, while WT cells persistently extended a broad lamella in the direction of movement. 2,28 Remarkably, neurons from hippocampus and retina transfected with a dominant negative PTP1B construct, displayed axonal growth cones with similar lamellar alterations as those observed in the leading edge of KO fibroblasts. Consistently, axons also showed reduced net elongation rate and increased pause times compared with axons of control neurons.…”
Section: Long-range Impact Of Ptp1b On Cell Adhesion and Motilitymentioning
confidence: 84%
See 2 more Smart Citations
“…A spatial subcellular gradient of the activity of PTP1B has been proposed to account for observations of its interactions with an artificial substrate 29 . The specific roles of ER-bound PTP1B at adhesions sites 30,31 and cell-cell junctions 32 have also been explored. These investigations highlight important and distinct physiological roles for PTP1B subpopulations distributed across the cell.…”
Section: Introductionmentioning
confidence: 99%